SYSTEM OF ORGANIZATIONAL AND ECONOMIC SUPPORT OF HUMAN RESOURCES MANAGEMENT AT ENTERPRISES - VALENTYNA YAKUBIV; ROMAN YAKUBIV (Vasyl Stefanyk Precarpathian National University, 2019)
The paper analyses various scientific approaches to the interpretation of the essence of the concept of "personnel management", defines the specific characteristics and principles of this process. For a detailed study of the essence and content of the concept of the personnel management, theoretical approaches to this definition and substantiation of its content in the context of various scientific schools and management theories are analysed. Scientific approaches to understanding the functional role and essence of the personnel management in various scientific schools are analysed, namely: schools of scientific management, classical (administrative) school of management, theory of perfect bureaucracy, school of human relations, empirical school of management, school of social systems, and "new school". The main differences in understanding the process of the personnel management in different theories of management are investigated, the main of which are: situational management theory; system theory of management; theory of organizational culture; theory of human resources management; theory of management culture. The relationship scheme and the place of the personnel management system in the enterprise management in general are substantiated. A three-level personnel management system for tactical, operational and ongoing tasks is proposed. The mechanism of organizational and economic support of the personnel management as a system of synergistically interconnected organizational and economic factors for establishing high-performance HR-management in the enterprise is substantiated. The main elements of organizational and economic support for improving the personnel management system of enterprises are scientific and theoretical approaches to the forming of this system; principles of personnel management; methods of labour management; functions of HR-management; economic levers; methodological support; information support; monitoring of personnel management.